Identifikasi Bahan Tambahan Makanan (BTM) yang ada di Pasar Puri Cipageran, Kota Cimahi - Isnatania, Alifianti Galih; Marsela Dwi Sabtiani, Anis; Adawiyah, Robiatul; Rahadatul ‘Aisy, Salsabila; Maharani, Shabrina; Asti Aristia, Syifa; Alpauzi, Pajri (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
ABTRACTBackground: In recent years, the misuse of hazardous chemicals such as formalin, borax and rhodamine B as food additives has become rampant. Although their use for food has been banned, there are various factors that encourage the misuse of these materials, one of which is due to the lack of knowledge of traders about the dangers of using these chemicals for the health of the body.Objective: to determine and analyze the presence or absence of formalin, borax and rhodamine B content in food ingredients in Puri Cipageran Market, North Cimahi District, Cimahi City. Method: experimental research method design, conducted at the Basic Chemistry Laboratory of the Faculty of Health Sciences and Technology (FITKES), General Achmad Yani University, Cimahi. Samples used in the form of food with a sampling technique that is simple random sampling sold by several traders who are in Puri Cipageran Market, North Cimahi District, Cimahi City. There were 5 food samples for Formalin content test, 5 food samples for borax test, and 5 food samples for rhodamine B test. Formalin, borax and rhodamine B were tested qualitatively. Data management was done descriptively and univariate analysis to see the percentage of formalin, borax, rhodamine B content in food. Results: Of the 15 food samples tested, the prevalence of formalin 0%, borax 0% and Rhodamine B 0% was obtained. So it can be said that the food sold at Cipageran Castle Market, North Cimahi District, Cimahi City is declared safe for consumption. Keyword: Foodstuff; Borax; Formalin; Rhodamine B